The impact of midlife on migraine in women: summary of current views - Jelena M. Pavlović (BMC, 2020)
Abstract Migraine is three times more common in women than in men and is the 4th leading cause of disability in women. Onset of migraine increases at menarche, with peaks in prevalence in the late 30s, and a rapid decline after menopause. While the prevalence is highest among women of childbearing age the frequency of headache and burden of migraine frequently worsens during midlife. Abundant population data suggest that hormonal factors may trigger headache attacks and influence onset and remission. The midlife worsening of migraine is attributed to hormonal fluctuations characteristic of the menopausal transition. Drops in estrogen presumably lead to increased migraine attacks at the time of menses as well as during the menopausal transition. During the menopausal transition, recommended approaches include both acute and preventive non-hormonal and hormonal options as well as behavioral approaches. Herein, is a brief review on the presentation of migraine in women across the lifespan, with special emphasis on midlife and the menopausal transition and implications for treatment.